The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1038/nchembio.1295
|View full text |Cite
|
Sign up to set email alerts
|

Pyrones as bacterial signaling molecules

Abstract: Bacteria communicate via small diffusible molecules and thereby mediate group-coordinated behavior, a process referred to as quorum sensing. The prototypical quorum sensing system found in Gram-negative bacteria consists of a LuxI-type autoinducer synthase that produces N-acyl homoserine lactones (AHLs) as signals and a LuxR-type receptor that detects the AHLs to control expression of specific genes. However, many proteobacteria have proteins with homology to LuxR receptors yet lack any cognate LuxI-like AHL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
180
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(192 citation statements)
references
References 46 publications
7
180
0
5
Order By: Relevance
“…Similar coupling reactions were reported for the non-homologous bacterial ketosynthases involved in the biosynthesis of 2,5-dialkylpyrones and 2,5-dialkylresorcinols (27)(28)(29)(30). For example, CorB and MxnB from the myxobacteria Corallococcus coralloides and Myxococcus fulvus catalyze the coupling of two ␤-ketoacyl diketide intermediates to produce the ␣-pyrone antibiotics corallopyronin and myxopyronin, respectively (27,28).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar coupling reactions were reported for the non-homologous bacterial ketosynthases involved in the biosynthesis of 2,5-dialkylpyrones and 2,5-dialkylresorcinols (27)(28)(29)(30). For example, CorB and MxnB from the myxobacteria Corallococcus coralloides and Myxococcus fulvus catalyze the coupling of two ␤-ketoacyl diketide intermediates to produce the ␣-pyrone antibiotics corallopyronin and myxopyronin, respectively (27,28).…”
Section: Discussionsupporting
confidence: 58%
“…For example, CorB and MxnB from the myxobacteria Corallococcus coralloides and Myxococcus fulvus catalyze the coupling of two ␤-ketoacyl diketide intermediates to produce the ␣-pyrone antibiotics corallopyronin and myxopyronin, respectively (27,28). Furthermore, in photopyrone biosynthesis in Photorhabdus luminescens, PpyS produces a signaling pyrone molecule in a similar manner (29). Conversely, the bacterial ketosynthase DarB catalyzes the coupling of a ␤-ketoacyl diketide intermediate and an ␣,␤-unsaturated acyl precursor, thereby generating the dialkylcyclohexanedione scaffold, which is further converted to 2,5-dialkylresorcinols by the aromatase DarA in Chitinophaga pinensis (30).…”
Section: Discussionmentioning
confidence: 99%
“…In general, six conserved amino acids in signal-binding domain of AHLsensing LuxR-type receptors are important for AHL binding. However, PauR and PluR only share two of them (Tyr66 and Asp75), which emerged as important for ligand sensing in all LuxR-type receptors (7,9). Other than these subtle differences, PauR and PluR are very closely related to AHL-sensing LuxRs (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acids Trp57, Tyr61, and Asp70 (positions with respect to TraR) interact with the oxygen of the amide group and the carbonyloxygen of the lactone, as well as the amide group-nitrogen, respectively (15,16). The observation that many LuxR homologs such as LuxR solos have substitutions of one or more of these six conserved amino acids originally prompted the idea that these proteins may sense signals other than AHLs, as recently demonstrated for PluR (7). In agreement with this observation, a sequence alignment of PauR and PluR against other receptors with homology to LuxR revealed that only two of six conserved amino acids (Tyr66, Asp75) are conserved in both proteins (Fig.…”
Section: Conserved Amino Acids In the Signal-binding Domain Of Paur Arementioning
confidence: 98%
“…Probably the answer is yes. An example is the recent identification of photopyrones produced by the insect pathogenic proteobacterium Photorhabdus luminescens (Brachmann et al 2013). These medium-sized lactones invoke a clumping behavior of the bacterial cells.…”
Section: # Springer Science+business Media New York 2014mentioning
confidence: 99%